EFFECT OF CARBAMIDE ON SERUM BIOCHEMICAL ASPECTS OF CHICK - V. UNICE SATYA LATHA,; M. RAJYASREE, (The Bioscan, 2012)
Impact of carbamide/Urea on Body weight, Total protein, Amino acids and Protease activity was studied in Gallus domesticus (Vanaraja) by exposing to 4.9% of carbamide dissolved in water for 15 and 30 days. carbamide showed differential effect on all parameters analysed. carbamide caused significant decrease in total body weight and serum total protein content, but an increase in Amino acid levels and neutral protease activity. The study indicates carbamide has negative impact on protein metabolism of chicken.